A detection panel of novel methylated DNA markers for malignant pleural effusion - Liang, Chaonan; Liu, Nan; Zhang, Qin; Deng, Mingming; Ma, Jiangwei; Lu, Jingwen; Yin, Yan; Wang, Jian; Miao, Yuan; She, Bin; Li, Qingchang; Hou, Gang (Frontiers in Oncology, 2022)
Background: Cytology remains the gold standard for the detection of malignant cells in pleural effusion. However, its sensitivity is limited. The aim of this study was to establish a novel panel of cancer-specific methylated genes for the differential diagnosis of malignant pleural effusion (MPE). Methods: A cohort of 100 cancer patients (68 lung cancer, 32 other malignant tumors) and 48 patients with benign disease presenting with pleural effusion was prospectively enrolled. Pleural effusion was evaluated by means of cytopathological investigation and DNA methylation of SHOX2, RASSF1A, SEPTIN9 and HOXA9 in the cellular fraction. DNA methylation in bisulfite-converted DNA was determined using quantitative methylation-specific real-time PCR (MS-PCR). Cytopathological and DNA methylation results were evaluated with regard to the final clinical diagnosis. Results: The LungMe® SHOX2 and RASSF1A Assay (Tellgen Corporation, China) has been reported to be highly sensitive and specific for lung cancer using bronchial aspirates. As expected, LungMe® detected metastases of lung cancer (sensitivity: 76.5%) as well as metastases of other malignant tumors (sensitivity: 68.8%). OncoMe, a novel combination of SHOX2, RASSF1A, SEPTIN9 and HOXA9 methylation, led to an additional 11% increase in the detection rate of MPE, resulting in a sensitivity of 85% and a specificity of 96%. Overall, OncoMe showed a higher positive detection rate in SCLC (100%), LUAC (87%), OC (100%), BC (92.9%), GC (80.0%), and MESO (80%) than in LUSC (50%). Cytopathological analyses only detected 23 positive samples, which were all positively measured by both LungMe® and OncoMe. Conclusion: OncoMe has potential for use as a biomarker for the detection of MPE, even not limited to lung cancer.